Mobile Screens The Visual Regime of Navigation - Verhoeff, Nanna (MediaMatters, 2012)
Nanna Verhoeff's new book is a must for anybody interested in visual culture and media theory. It offers a rich and stimulating theoretical account of the central dimension of our contemporary existence - interfacing and navigating both data and physical world through a variety of screens (game consoles, mobile phones, car interfaces, GPS devices, etc.) In the process of exploring these new screen practices, Verhoeff offers fresh perspectives on many of the key questions in media and new media studies as well as a number of new original theoretical concepts. As the first theoretical manual for the society of mobile screens, this book will become an essential reference for all future investigations of our mobile screen condition. - Lev Manovich